Identify the relationship of organizational culture towards employee performance in dinas pemuda & olahraga (dispora) kota bandung - Rifqi, Fuadur; Pritasari, Adita (Journal of Business and Management, 2019)
There have been many literature reviews to search the impact the of organization culture on employee performance. Researchers have related culture within the organization to many distinct organizational behaviors, as well as recognizing the correlation between organizational culture and employee performance. In Indonesia's public/government organizations, the performance of civil servants is very crucial in creating good governance and clean governance, and in supporting government duties in providing the best service to the public on the basis of its features as a public service. One of today's major problems for civil servants is to operate effectively and efficiently as government agencies in Indonesia. The aim of this study is to investigate the identification of powerful organizational culture dimensions that enhance the employee performance in Dinas Pemuda & Olahraga (Dispora) Kota Bandung. This study results may provide relevant information for organization to understanding the role of organization culture. The findings of the study may positively affect organization by providing strategies to improve their employee performance. This research using quantitative approach through questionnaire and SPSS to process the questionnaire result. The result in this search is Organization culture has positive impact towards employee performance in Dispora and Communication pattern is dominant factor of organization culture that can improve employee performance in Dispora. The management of Dispora Organization leader in Dispora need to state organization culture clearly, through written behavioral guideline to create better understanding for employee to do their job. Keywords: Organization Culture, Employee Performance,Dinas Pemuda & Olahraga Kota Bandung